Microstrip patch antenna with defected ground structure for biomedical application - Islam, Md. Shazzadul; Ibrahimy, Muhammad Ibn; Motakabber, S. M. A.; Hossain, A. K. M. Zakir; Azam, S. M. Kayser (Universitas Ahmad Dahlan in collaboration with IAES Indonesia Section, 2019)
Proper narrowband antenna design for wearable devices in the biomedical application is a significant field of research interest. In this work, defected ground structure-based microstrip patch antenna has been proposed that can work for narrowband applications. The proposed antenna works exactly for a single channel of ISM band. The resonant frequency of the antenna is 2.45 GHz with a return loss of around -30 dB. The -10 dB impedance bandwidth of the antenna is 20 MHz (2.442-2.462 GHz), which is the bandwidth of channel 9 in ISM band. The antenna has achieved a high gain of 7.04 dBi with an increase of 17.63% antenna efficiency in terms of realized gain by using defected ground structure. Three linear vector arrays of arrangement 1x2, 1x4 and 1x8 have been designed to validate the proposed antenna performances as an array. The proposed antenna is light weighted, low cost, easy to fabricate and with better performances that makes it suitable for biomedical WLAN applications.